2022
DOI: 10.1002/adfm.202210867
|View full text |Cite
|
Sign up to set email alerts
|

Proximity Electronic Effect of Ni/Co Diatomic Sites for Synergistic Promotion of Electrocatalytic Oxygen Reduction and Hydrogen Evolution

Abstract: The modulation effect manifests an encouraging potential to enhance the performance of single‐atom catalysts; however, the in‐depth study about this effect for the isolated diatomic sites (DASs) remains a great challenge. Herein, a proximity electronic effect (PEE) of Ni/Co DASs is proposed that is anchored in N‐doped carbon (N‐C) substrate (NiCo DASs/N‐C) for synergistic promoting electrocatalytic oxygen reduction reaction (ORR) and hydrogen evolution reaction (HER). Benefiting from the PEE of adjacent Ni anc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
52
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(54 citation statements)
references
References 45 publications
2
52
0
Order By: Relevance
“…180,181 Both processes need efficient catalysts, and thus numerous heterogeneous homo- and heteronuclear DMCs have been developed. 182–220…”
Section: Dmsc For Energy Conversion In Heterogeneous Catalytic Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…180,181 Both processes need efficient catalysts, and thus numerous heterogeneous homo- and heteronuclear DMCs have been developed. 182–220…”
Section: Dmsc For Energy Conversion In Heterogeneous Catalytic Systemsmentioning
confidence: 99%
“…The in situ characterization and theoretical calculation results indicated that the Co atom served as the active site for O 2 adsorption–activation, and the adjacent Ni site acted as a modulator to promote *OH and *H adsorption on the Co site, thus significantly boosting the ORR activity. 198…”
Section: Dmsc For Energy Conversion In Heterogeneous Catalytic Systemsmentioning
confidence: 99%
“…[16,[25][26][27][28][29] Another effective approach is to construct SAs with two different transition metals through the synergetic effect of dual-metal sites to modulate the electrocatalysts' activity. [30][31][32][33][34][35][36][37][38] Such an approach takes advantage of the two isolated metal sites by pairing or long-range coupling to modulate the coordination and electronic structures, which correlates with the adsorption/desorption behavior of relevant oxygen intermediates. [39][40][41][42][43] However, a comprehensive study of the synergetic effect of isolated dual-metal sites has not been explored in most studies.…”
Section: Introductionmentioning
confidence: 99%
“…27−29 Furthermore, most recently, as a strategy to achieve efficient HER activity, single-atom transition metals have been dispersed to form productive transition metal and nitrogen bonds. 30,31 Among all transition metal materials, transition metal nitrides (TMNs) have shown promising results as electrocatalysts for alkaline HER activity because of their great inherent corrosion stability in alkaline media, high binding capability to atomic hydrogen, and low electrical resistance. 32,33 To date, Ni (Ni 3 N), are the most commonly used for H 2 production (HER) in alkaline electrolyzers because of their higher electronic conductivity (≈ 0.1 S/m); additionally, electronegative nitrogen (N) atoms act as a base to trap H* adsorption, which facilitates the HER activity.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Moreover, even the noble metal Pt has exhibited lower activity in alkaline media because of the additional sluggish water (H 2 O) dissociation step as the proton (H*) source . Consequently, great research efforts have been devoted to the development of Pt-free HER electrocatalysts based on transition metal materials, including metal alloys, chalcogenides, phosphides, carbides, , and nitrides. Furthermore, most recently, as a strategy to achieve efficient HER activity, single-atom transition metals have been dispersed to form productive transition metal and nitrogen bonds. , …”
Section: Introductionmentioning
confidence: 99%